Training teacher-tutors for developing giftedness in children during research - Zinovyeva Tatiana Ivanovna; Afanasyeva Zhanna Viktorovna; Bogdanova Antonina Vladimirovna; Leonovich Evgeniy Nikolaevich (SHS Web of Conferences, 2021)
The article deals with the issues of teacher training in the higher education system. The purpose of the study is to justify the possibility of forming a pedagogue’s readiness for tutor support of students’ research in the context of developing giftedness in children. The prerequisites for the study are the challenges of the rapidly changing society and the resulting focus of the education policy on nurturing professionals who are competitive in the labor market, increased interest of researchers and organizers of the higher education system in the search for ways to increase the training quality of specialists in every area of social life including the training of specialists in pedagogy. Scholarly achievements in the development of a teacher’s professionalism, tutor support in the education process, teaching research, and promotion of giftedness in children are also key factors in the study. The main research method is the method of theoretical analysis of scientific pedagogical and psychological-pedagogical literature. The authors have selected and explored a substantial set of sources in Russian and English published predominantly over the last five years in science-driven databases such as the Russian Science Citation Index, Web of Science, Scopus, and other peer-reviewed outlets. Results and novelty: the context of the recent developments in pedagogical science in the field of training professionals is adequate to the trends and goals of modern education – the inclusion of student teachers in the actual practice of tutor support of students, the organization of teaching research to schoolchildren, and the development of giftedness in children. The solution to these problems is ensured by streamlining the educational process at the university based on a universal model for developing the teacher’s professionalism, through the implementation of the reflexive and activity-based approach.